Anode effect and МHD-instability in aluminium electrolyzer. Control of parameters for their prognosis - Щербань, Геннадий Иванович; Червоный, Иван Федорович (Eastern-European Journal of Enterprise Technologies, 2014)
The results of studying the interaction of the complex of process parameters on the occurrence and course of the "anode effect", using which will allow to significantly improve the electrolysis process and increase the electrolyzer efficiency were presented. With the appearance of the "anode effect", the current density on the free surface greatly is increased, the anode potential becomes more positive and is passivated to the potential, sufficient for the discharge of fluorine ions, fluorine ions with oxygen ions at the anode start to be discharged, the concentration of perfluorocarbons increases up to 30%. Interaction of the magnetic field with the current appears not only in the misalignment of the molten metal surface. The studies of magnetohydrodynamic processes in the electrolyzer have shown that the molten metal surface is in a state of continuous agitation and herewith the wave height can reach 45 mm. Thus, the wave height is comparable to the interpolar distance, which causes local short-circuiting. To minimize the number of process abnormalities on the electrolyzer, the necessity of constant monitoring of a number of parameters that characterize the current state and development of abnormalities in the bath: temperature of the electrolyte and its overheating; concentration of alumina; composition of the anode gas and the ratio of CF4, CO, CO2 in flue gases; back EMF and the specific resistivity of the electrolyte; interpolar distance, height of the metal and electrolyte; ratio of the melt densities of the electrolyte and aluminum; thickness of the ledge; effective current density and its distribution under the anode face; distribution of current intensity and magnetic field in hearth; change in the shape of the working space was established.